Answer:
$0.02
Step-by-step explanation:
1.28/64
Answer:
The only possible answer that is correct is the first one, x = -4.
Step-by-step explanation:
Simplify the given inequality as much as possible, and then substitute each of the given x values one by one to determine which is in the solution set.
9(2x + 1) < 9x - 18 becomes 18x + 9 < 9x - 18, which, if reduced by dividing all four terms by 9, becomes 2x + 1 < x - 2.
Simplifying further, we get x < - 3. The only possible answer that is correct is the first one, x = -4. -4 < -3 is true.
Answer:
love i hate and i will not pecherate
Step-by-step explanation:
-2 and+2 =0
1/2 -3/2= -2/2 or -1
7-1=6
Answer:
see below
Step-by-step explanation:
The point-slope form of the equation of a line is ...
y -h = m(x -k)
for a line with slope m through point (h, k).
Comparing this to the given equation, you see that ...
h = -2, m = 1, k = -4
The line has a slope of 1 and goes through the point (-4, -2). This information is useful for graphing.
__
You can also rearrange the equation to slope-intercept form by subtracting 2 from both sides.
y = x +2
This has a slope of 1 and crosses the y-axis at y=2. It graphs the same as the above.